Regulation, Reform and the Question of Democratising the Broadcast Media in Thailand - Siriyuvasak, Ubonrat (Javnost-The Public, 2001)
This paper discusses the struggle for the democratisation of the broadcast media in the context of the social and political reform in Thailand during 1997-2000. A new law to set up an independent regulatory body was enacted in March 2000. The gist of the legislation is to restructure state ownership of the broadcasting media and to re-allocate them into three categories of ownership. These are state, commercial and community licenses. The unprecedented change in the law came about after Article 40 of the 1997 Constitution stipulated that radio spectrum for radio and television transmission and radio communications are national resources to be used for public interests. Although the new Constitution has effectively brought about legal reform in the media law the actual process of structural and institutional transformation have yet to take shape. There are indications that the state agencies owning radio and television stations are against the re-structuring of their ownership rights. On the other hand, large private media operators are eager to become the new player in the industry at all costs. Allying themselves with the influential state agencies they stepped in together to control the selection process of the National Broadcasting Commission (NBC). This leaves the community sector, whose right has been guaranteed by law, in a perilous and exposed position. The liberalising process will bring about a further privatisation of radio and television, since the new commercial licenses are expected to transfer state ownership right or state property into private property. In addition, the television and radio stations operated by the state agencies will be commercialised.